Evaluation of Effects of Different Concentrations of Lead, Alcohol and Vitamin E on Protein Carbonyl Content of Brain Tissue in Rats - Anusuya MR, Kiran B (Journal of Applied Pharmaceutical Science)
The lead treatment was characterized by increase (28%) in protein carbonyl content 5.19, but the increase was not significant. In alcohol treated rats, the protein content was 5.52nmol/gram of brain tissue of rat. The increase (36%) was significantly higher when compared to lead treated rats. The protein carbonyl content (6.39nmol/gram) was further increased in rats coexposed to alcohol and lead, and the values ranged from 5.40 to 8.20 nmol/gram. The percent increase in protein carbonyl content was 57% in rats coexposed to alcohol and lead. Thus, the magnitude of deleterious effects of oxidative stress on protein oxidation is more significant in combined treatment group when compared to lead alone treated rats and alcohol alone treated rats. The lead treatment was characterized by a significant increase (37%) in protein carbonyl content (6.19nmol/gram). In alcohol treated rats, the increase in protein carbonyl content (6.79nmol/gram) was more marked (51%) when compared to lead treated rats. The protein carbonyl content was significantly increased (73%) in rats coexposed to alcohol and lead, and the values ranged from 6.80 to 8.56 nmol/gram (7.76nmol/gram).
Keywords: Lead, Alcohol, Vitamin E, Protein, Brain tissue.